A new mutation in the TYMP-gene: clinical and morphological characteristics of a patient with MNGIE syndrome - S. N. Bardakov; I. S. Limaev; A. M. Emelin; V. Nikitins; E. V. Presnyakov; S. A. Kurbatov; P. G. Tsygankova; V. A. Tsargush; I. A. Chekmareva; E. V. Kolmakova; N. V. Bakulina; R. V. Deev (Нервно-мышечные болезни)
Mitochondrial neurogastrointestinal encephalomyopathy is an extremely rare (1–9:1 000 000, Orphanet, 2021) multisystem genetic disease caused by mutations in the TYMP gene encoding the enzyme thymidine phosphorylase.The article presents the data of a thirteen‑year survey on 40‑year‑old patient D. with clinical manifestations of mitochondrial neurogastrointestinal encephalomyopathy syndrome associated with the previously undescribed missense mutation c.1301G>T (p.Gly434Val) of the TYMP gene. Detailed clinical picture (gastrointestinal dysfunction, cachexia, blepharoptosis, ophthalmoparesis, peripheral polyneuropathy and leukoaraiosis), electroneuromyography data (demyelination with secondary axonopathy), high blood serum level of dihydrothymine together with normal levels of thymidine and deoxyuridine made it possible to verify the diagnosis. Histopathological examination revealed atrophy of the longitudinal (outer) muscle layer of the small and large intestines and a significant decrease in the number of CD117+ cells (telocytes), signs of damage to the striated skeletal muscles of a mixed nature with a predominance of the myogenic pattern, as well the destruction of the myelin sheaths of peripheral nerves. Histochemical examination did not reveal “ragged red fibers” characteristic of mitochondrial pathology. Transmission electron microscopy demonstrated the presence of megalomitochondria in the myocardium.